ANALISIS PROSES BERPIKIR SISWA DALAM MEMECAHKAN MASALAH MATEMATIKA DITINJAU DARI GAYA KOGNITIF FIELD DEPENDENT DAN FIELD INDEPENDENT - Dyah Kartikasari, Agatha Ika (JIEM | JURNAL ILMIAH EDUKASI MATEMATIKA, 2017)
This research aims to describe the characteristics of students’ thinking process in resolving mathematics problems based on cognitive style theory – Field Dependent (FD) and Field Independent (FI). This research design of this study is explorative descriptive research. Therefore, it is not aimed to clarify hypothesis. The data used in this research is qualitative one. They are taken from the research subjects which are the students of VIII-H class in Junior High School 1 Madiun of the academic year of 2016/2017. The research subjects of this study are determined by distributing Group Embedded Figure Test (GEFT) to them. Then, the students are selected to fulfill the criteria for being research subject which is based on the cognitive style they possessed. The data collection technique is conducted by using Think Alouds (Think Out Loud) method and clinical interview. The data analysis technique of this study is a descriptive analysis. It is performed by interpreting every step of thinking which is considered and acquired by the research subjects as they deal with the mathematics problems. According to the research result, the researcher can conclude the characteristics of students’ thinking processes which have cognitive style of Field Dependent (FD) and of students’ thinking processes which have cognitive style of Field Independent (FI) in resolving the mathematics problems.